Exploring Liraglutide’s mechanism in reducing renal fibrosis: the Fsp1-CoQ10-NAD(P)H pathway - Qi Chen; Ji-Xian Song; Zhi Zhang; Ji-Ren An; Yu-Jing Gou; Miao Tan; Yashuo Zhao (Scientific Reports)
Abstract Studies have confirmed that elevated glucose levels could lead to renal fibrosis through the process of ferroptosis. Liraglutide, a human glucagon-like peptide-1 (GLP-1) analogue, is a potential treatment option for diabetes. This study aimed to examine the potential of liraglutide (LIRA) in inhibiting ferroptosis and reducing high glucose-induced renal fibrotic injury in mice, and whether the Fsp1-CoQ10-NAD(P)H signal pathway is a mechanism for this effect. In our study, we used db/db mice to simulate Type 2 diabetes mellitus (T2DM). The mice were intraperitoneally injected with LIRA (200 µg/kg/d) daily for 6 weeks. Renal function, pathologic changes, lipid peroxidation levels, iron levels, and ferroptosis were assessed. First, LIRA ameliorated renal dysfunction and fibrosis in db/db mice. Second, LIRA inhibited lipid peroxidation by up-regulating T-SOD, GSH-Px, and GSH activities as well as down-regulating the levels of 8-OHDG, MDA, LPO, 4-HNE, 12-Lox, and NOX4 in db/db mice. In addition, LIRA attenuated iron deposition by decreasing the expression of TfR1 and increasing the expression of FPN1. Meanwhile, LIRA reduced high levels of high glucose-induced cell viability decline and intracellular lipid peroxidation. Furthermore, LIRA inhibited ferroptosis by adjusting the Fsp1-CoQ10-NAD(P)H pathway in vivo and in vitro. These findings suggested that LIRA attenuated kidney fibrosis injury in db/db mice by inhibiting ferroptosis through the Fsp1-CoQ10-NAD(P)H pathway.